The Study and Achieving of High-precision Data-acquisition Based on ΔΣADC - SU Shu-jing; ZHANG Hai-li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
ΔΣ ADC is used more and more widely, and it is favored for the important reason of high precision. In this paper, working principle and characteristics of ΔΣ modulator and digital filter have been analyzed, and then oversampling, noise shaping and digital filtering characteristics are discussed. Finally, a practical application is illustrated and its basic structure of acquisition circuit is given, the design ideas of single-ended-to-differential driver circuit and front RC filter circuit is highlighted, and the choosing of connection method of multiple channel system is argued. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3048